2020
DOI: 10.37696/nkmj.781331
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye'de COVID-19 pandemisi sırasında sağlık çalışanlarında ve çocuklarında anksiyete belirtileri

Abstract: Infectious disease outbreaks not only affect the physical health of patients but also affect the psychological health and well-being of the uninfected population. High rates of psychiatric symptoms and stress are observed in the general population in COVID-19 pandemic and healthcare workers (HCWs) reported higher-risk perception and anxiety level. We aimed to evaluate the anxiety levels of HCWs and their children during the COVID-19 pandemic in Turkey. Materials and Methods: A total of 121 HCWs and 121 HCWs' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(46 reference statements)
1
4
0
Order By: Relevance
“…A different study that investigated the anxiety levels and sleeping problems of children of healthcare workers who had COVID‐19 reported that some anxiety problems, independent of COVID‐19, had been observed in these children; the same study also reported that parents' being apart from home during the pandemic is a predictor of children's sleeping disorders 19 . This study also determined that there is a positive correlation between the anxiety of healthcare workers and their children; this correlation may explain the negative changes observed in children's daily life activities in the present study 18 …”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…A different study that investigated the anxiety levels and sleeping problems of children of healthcare workers who had COVID‐19 reported that some anxiety problems, independent of COVID‐19, had been observed in these children; the same study also reported that parents' being apart from home during the pandemic is a predictor of children's sleeping disorders 19 . This study also determined that there is a positive correlation between the anxiety of healthcare workers and their children; this correlation may explain the negative changes observed in children's daily life activities in the present study 18 …”
Section: Discussionsupporting
confidence: 70%
“…19 This study also determined that there is a positive correlation between the anxiety of healthcare workers and their children; this correlation may explain the negative changes observed in children's daily life activities in the present study. 18 In a study that compared the anxiety and depression levels of children (aged 9-17 years) of healthcare workers with those of nonhealthcare workers' children (also aged 9-17 years) in the first year of the pandemic, no significant difference was detected between the two groups in terms of their levels of depression levels.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is noted that psychological problems in health care professionals may also be associated with various physical symptoms, such as headaches, and may have a negative impact on the daily functioning of health care professionals (Chew et al, 2020). A study conducted in health care professionals in Turkey also found higher levels of anxiety, similar to those in the world, but also associated it with anxiety observed in their children (Şahin et al, 2020).…”
Section: Introductionmentioning
confidence: 63%